ISSP position stand: To test or not to test? The use of physical skill tests in talent detection and in early phases of sport development - Lidor, R.; Côté, J.; Hackfort, D. (International Journal of Sport and Exercise Psychology, 2009)
A Searching for talent and the assessing ability in young prospects from individual and team sports often include measurement, analysis, and evaluation of physical and motor skills. The use of these tests in early stages of talent development has been widely observed in both female and male prospects. The purpose of this paper is to review a series of studies conducted on talented and less-talented athletes/players that were aimed at distinguishing between the two groups and at predicting the athletes`/players` future achievements/success. Thirteen studies examining the use of physical and motor skill tests in young prospects are reviewed. Based on this review, four main observations are highlighted and a number of benefits and limitations associated with the use of such tests are discussed. It is recommended that (1) coaches reduce the number of batteries of physical and motor skill tests used in early phases of talent development and (2) coaches and sport scientists specializing in measurement and evaluation cooperate in order to improve the effectiveness of the application and interpretation of physical skill tests given to prospects at early stages of talent development.